Do functional scores of flap donor sites recover after reconstruction of segmental jaw defects? - Shavlokhova, Veronika; Mertens, Christian; Engel, Michael; Hoffmann, Jürgen; Freier, Kolja (Journal of oral and maxillofacial surgery, 2020)
The potential for donor-site morbidity in major maxillofacial reconstruction remains a concern. The purpose of this study was to compare the outcome of donor-site morbidity of deep circumflex iliac artery (DCIA) and scapula free flaps after radical treatment of the jaw and flap reconstruction. Patients and Methods We implemented a prospective cohort study design. Patients requiring segmental resection for benign pathology underwent reconstruction with either DCIA or scapula free flaps. The primary predictor variable was the use of DCIA versus scapula free flaps. The primary outcome variables were changes in orthopedic functional scores for both donor sites. The secondary outcome variable was neurosensory recovery at the recipient site. Results We included 8 patients in this study, comprising 3 women (38%) and 5 men (62%). Orthopedic scores were assigned preoperatively (T0) and at follow-up appointments at 1 to 3 months postoperatively (T1) and 6 to 12 months postoperatively (T2). In patients with DCIA flaps, a significant reduction (P = .0096) in the Larson I score between examination time points T0 and T1 was found. The score then improved on the operated side between T1 and T2 by an average of 29 points and showed no significant difference compared with the T0 level (P = .68). Patients with a scapular graft showed a significant reduction (P = .004) in the Constant-Murley score on the operated side between T0 and T1. The Constant-Murley score again improved significantly (P = .0136) between T1 and T2. Most of the patients (n = 7, 88%) had a neurologically unremarkable local situation of the recipient site at T0. At T1, 1 patient had level A (mild) neurosensory disorder and 1 had level B (moderate). At T2, all patients' initial neurologic scores were restored. Conclusions The donor-site morbidity associated with DCIA and scapula flap reconstruction is a short-term condition and returns to baseline by 3 to 6 months postoperatively.